2022
DOI: 10.1007/s00345-021-03920-1
|View full text |Cite
|
Sign up to set email alerts
|

First completely robot-assisted retroperitoneal nephroureterectomy with bladder cuff: a step-by-step technique

Abstract: Introduction While various surgical techniques have been reported for open and minimally invasive treatment of upper tract urothelial cancer (UTUC), the procedure of robot-assisted nephroureterectomy (NU) with bladder cuff has never been reported using only retroperitoneum without entering abdominal cavity. We developed a novel port placement and technique allowing to perform robot-assisted NU by a unique retroperitoneal approach. Methods Between February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Average console time for those undergoing rRN was 198 minutes, and one patient undergoing rRSN requiring open conversion for non-progression. Lastly, Sparwasser et al reported on five patients who underwent rRNU using a similar technique described in this current study ( 18 ). While mean operative time in that group was only 189 minutes compared to 233 minutes in our study, their average patient was not obese.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Average console time for those undergoing rRN was 198 minutes, and one patient undergoing rRSN requiring open conversion for non-progression. Lastly, Sparwasser et al reported on five patients who underwent rRNU using a similar technique described in this current study ( 18 ). While mean operative time in that group was only 189 minutes compared to 233 minutes in our study, their average patient was not obese.…”
Section: Discussionmentioning
confidence: 56%
“…There have only been three publications to our knowledge on the use rRN ( 18 , 29 , 30 ). Rose et al reported on the use of the Da Vinci S platform to perform a retroperitoneal nephroureterectomy on two patients with a hybrid port technique ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sparwasser et al published the first series of completely retroperitoneal robot-assisted radical nephroureterectomy (RRNU) [ 16 ], and subsequently compared this technique to the standard transperitoneal approach [ 17 ]. In this scenario, ports placement starts from the Petit’s triangle and then follows a line above the iliac crest ( Figure 2 ).…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Indeed, a major hurdle to this approach is difficulty in MP placement and subsequent instrument clashing, making the operation burdensome and difficult to replicate. Of note, at the time of publishing this article, there is only a single publication describing a completely retroperitoneal robotic NU with bladder cuff excision, authored by Sparwasser et al , who performed surgery on 5 patients using the daVinci Xi ( 11 ). Here, the patient was placed in a lateral flank position and the trocars were placed parallel to the costal arch, following a line mimicking Kocher’s incision, with subsequent balloon dilation used to create space to accommodate the different robotic arms.…”
Section: Introduction: the Challenges Faced By The Multi-port (Mp) Ro...mentioning
confidence: 99%